Efectos de la pandemia por COVID 19 en la demografía empresarial del Perú, periodo 2020 - Del Águila López, Jack Raymundo (2021)
On March 16, 2020, the government authorities decided to shut down the economy and declare a curfew to combat the spread of the COVID 19 pandemic, which began to gradually reopen from July of the same year. The objective of this research is to determine the effects of the COVID 19 pandemic on the business demography of Peru, in the 2020 period. Guided by this purpose, the present study of Quantitative type, Descriptive level and design is carried out No Experimental. The investigation concludes that the COVID 19 pandemic did not reduce the business mass in Peru in 2020, since at the beginning of the year the business stock was 2,734,619 units and in December it reached 2,777,424; showing an increase of 42,805 companies, equivalent to 1.57%. The economic activity that had the highest number of casualties was "Retail Trade", having reported that 11,638 companies stopped operating in the referred period, representing 25.60% of the total. The companies located in this category show a low net worth. The legal organization that registered the most casualties was "Natural Person", due to the cessation of operations of 32,738 companies, which is equivalent to 72% of the total. According to the type of registration, the highest number of company registrations occurred in the “Natural Person” category with 145,847 units (78.05%); and the highest number of casualties also in "Natural Person" with 7,264 companies (98.72%).